2021
DOI: 10.1177/17411432211001365
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the sources of self-efficacy by Flemish school principals in primary education

Abstract: Self-efficacy is a perceived judgment that one has the ability to execute a course of action that brings about a desired result. While a growing body of research demonstrates the importance of self-efficacy by school leaders, little is known about the different sources of principals’ self-efficacy. This qualitative study investigates the relevance of Bandura’s sources of self-efficacy and on potential additional sources. The analysis is based on semi-structured interviews with 23 primary school principals in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Understandably, intensive communication during school closures increased the workload for most school leaders in Kazakhstan, similar to international evidence (Bellemans et al, 2023; Kristensen et al, 2024). Although past research does not address the correlation between high work intensity and school types, location, and school leader gender, the current study reveals that urban school leaders faced a significant increase in their workload compared to their rural counterparts.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Understandably, intensive communication during school closures increased the workload for most school leaders in Kazakhstan, similar to international evidence (Bellemans et al, 2023; Kristensen et al, 2024). Although past research does not address the correlation between high work intensity and school types, location, and school leader gender, the current study reveals that urban school leaders faced a significant increase in their workload compared to their rural counterparts.…”
Section: Discussionsupporting
confidence: 75%
“…Firstly, while previous international literature has highlighted how teachers’ insufficient digital competence impacted the effectiveness and frequency of online lessons during school closures (König et al, 2020; Lepp et al, 2021), the current study extends our understanding of how school leaders addressed this issue by supporting teachers’ digital literacy and navigating disparities in professional development opportunities. Secondly, while prior international research has recognized the significance of maintaining regular lines of communication with stakeholders, including parents (McLeod & Dulsky, 2021), resulting in school leaders’ workload intensity (Bellemans et al, 2023; Kristensen et al, 2024), the current study has identified the unequal distribution of the burden of intensive communication among school leaders. Thirdly, while existing literature has touched on teacher autonomy in academic matters during the pandemic (Azhari & Fajri, 2022; Chang et al, 2022; Keese et al, 2022; Kramer et al, 2023), this study examined the intersection of leadership practices regarding autonomy with school type, location, and school leaders’ gender.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…According to Bellemans & Devos (2021), they analyzed Bandura's sources of self-efficacy and speculated on possible additional factors. Despite being mostly little triumphs that don't pertain to anything particularly noteworthy, the findings show that mastery experiences appear to be the most significant source of primary selfefficacy.…”
Section: Self-efficacymentioning
confidence: 99%